Rancang Bangun Soft Star Motor Induksi Tiga Fasa degan Metode Detektor Pengendalian Sudut Fasa Berbasis Mikrokontroler - Syahrizal; Syamsir, Hendri Novia (Politeknik Caltex Riau, 2023)
Induction motors are the most common type of motor used in industry and in households with several advantages including simple construction and easy maintenance. However, induction motors also have weaknesses, one of issue is use large starting currents in a short time which can cause voltage drops in the power grid. This research focuses on the design and manufacture of a soft starter in order to suppress the start current surge. The method used by control the firing angle of the triac using a trigger circuit that is controlled by an arduino with optocouper as the phase detector. By adjusting the ignition angle of the triac, the voltage during the motor starting process can be adjusted. In addition, this softstarter can adjust the length of time the motor starts from 0 volts to the nominal voltage. The instrument testing was carried out on a 3-phase induction motor with a power specification of 1HP and a nominal current of 2 A with a start time varying between 3 seconds, 7 seconds and 10 seconds. From the test results obtained a linear increase in the motor input voltage with respect to the time set. During the process of increasing the voltage, in the T phase there is a slight difference in value to the other 2 phases, but at the end of the starting process the voltages of the three phases return to the same value. Meanwhile, the starting current tends to follow a voltage increase by linear but fluctuating with starting current lowest than DOL starter method. Keywords: soft start, triac, trigger, arduino, phase angle, induction motor